Network Expansion to Mitigate Market Power: How Increased Integration Fosters Welfare - Alexander Zerrahn; Daniel Huppmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Lack of transmission capacity hampers the integration of the European electricity market, and thereby precludes reaping the full benefits of competition. In this work, we investigate the extent to which transmission grid expansion promotes competition, efficiency and welfare. To this end, we propose a three-stage model for grid investment: a benevolent planner decides on network upgrades, considering welfare benefits of investments through a reduction of market power exertion by strategic generators. These firms anticipate their impact on market clearing, in particular when lines are congested. In this respect, we provide the first model effectively endogenizing the trade-off between costs of grid investment and benefits from reduced market power potential. In a three-node network, we illustrate three distinct strategic effects: firstly, by reducing market power exertion, network expansion can promote welfare beyond pure efficiency gains: optimally accounting for strategic generator behavior can push welfare close to a first-best competitive benchmark. Myopically focusing on bottlenecks only can yield suboptimal outcomes. Secondly, network upgrades entail a relative shift of rents from producers to consumers, and thirdly, they may yield suboptimal or even disequilibrium outcomes when strategic behavior of certain market participants is neglected in network investment.
Is replaced by the following version: http://hdl.handle.net/10419/201412
Keywords: L13; L51; C61; 330; market power; electricity transmission; network expansion; Generalized Nash equilibrium (GNE); mixed-integer equilibrium problem under equilibrium constraints (MIEPEC)